Caspase-3 Activation Correlates With the Initial Mitochondrial Membrane Depolarization in Neonatal Cerebellar Granule Neurons - Benítez-Rangel, Edaena; Olguín-Albuerne, Mauricio; López-Méndez, María Cristina; Domínguez-Macouzet, Guadalupe; Guerrero-Hernández, Agustín; Morán, Julio (Frontiers in Cell and Developmental Biology, 2020)
In this study we evaluated the effect of the reduction in the endoplasmic reticulum calcium concentration ([Ca2+]ER), changes in the cytoplasmic calcium concentration ([Ca2+]i), alteration of the mitochondrial membrane potential, and the ER stress in the activation of caspase-3 in neonatal cerebellar granule cells (CGN). The cells were loaded with Fura-2 to detect changes in the [Ca2+]I and with Mag-fluo-4 to measure variations in the [Ca2+]ER or with TMRE to follow modifications in the mitochondrial membrane potential)in response to five different inducers of CGN cell death. These inducers were staurosporine, thapsigargin, tunicamycin, nifedipine and plasma membrane repolarization by switching culture medium from 25 mM KCl (K25) to 5 mM KCl (K5). Additionally, different markers of ER stress were determined and all these parameters were correlated with the activation of caspase-3. The different inducers of cell death in CGN resulted in three different levels of activation of caspase-3. The highest caspase-3 activity occurred in response to K5. At the same time, staurosporine, nifedipine, and tunicamycin elicited an intermediate activation of caspase-3. Importantly, thapsigargin did not activate caspase-3 at any time. Both K5 and nifedipine rapidly decreased the [Ca2+]i, but only K5 immediately reduced the [Ca2+]ER and the mitochondrial membrane potential. Staurosporine and tunicamycin increased the [Ca2+]i and they decreased both the [Ca2+]ER and mitochondrial membrane potential, but at a much lower rate than K5. Thapsigargin strongly increased the [Ca2+]i , but it took 10 min to observe any decrease in the mitochondrial membrane potential. Three cell death inducers -K5, staurosporine, and thapsigargin- elicited ER stress, but they took 30 min to have any effect. Thapsigargin, as expected, displayed the highest efficacy activating PERK. Moreover, a specific PERK inhibitor did not have any impact on cell death triggered by these cell death inducers. Our data suggest that voltage-gated Ca2+ channels, that are not dihydropyridine-sensitive, load the ER with Ca2+ and this Ca2+ flux plays a critical role in keeping the mitochondrial membrane potential polarized. A rapid decrease in the [Ca2+]ER resulted in rapid mitochondrial membrane depolarization and strong activation of caspase-3 without the intervention of the ER stress in CGN.